An interrupted time series analysis of the differential impact of New Jersey’s BAC legislation on driver and passenger crash fatalities - Chamlin, Mitchell B. (Journal of crime and justice, 2017)
Most research, drawing on deterrence and rational choice models of social action, examines the effects of reductions of blood alcohol concentration [BAC] limits to secure drunk driving convictions on the total volume of crash fatalities. This paper extends this work by investigating the impact of New Jersey’s BAC legislation on total and disaggregated crash fatalities. The results from the interrupted times series analyses show that reducing the BAC limit to 0.8 has no effect on total or driver fatalities, but has a negative and lasting effect on passenger fatalities. The implications of these findings for future research are discussed.